Bridging Gaps in Migraine Management: A Comprehensive Review of Conventional Treatments, Natural Supplements, Complementary Therapies, and Lifestyle Modifications - Fatma Abo-Elghiet; Heba Elosaily; Doha K. Hussein; Riham A. El-Shiekh; Ashraf A’aqoulah; Einas M. Yousef; Heba Mohammed Refat M. Selim; Ahmed M. El-Dessouki (Pharmaceuticals)
Background: Migraine, a complex neurological condition, poses significant challenges for both sufferers and healthcare providers. While prescription medications play a vital role in managing migraine attacks, the quest for natural, non-pharmacological alternatives has garnered increasing interest. This review explores the efficacy and safety of natural supplements as treatments for migraine relief, comparing them with conventional prescription medications. Methods: The review delves into herbal supplements, clinical studies on natural remedies, aromatherapy, dietary influences, and lifestyle modifications in the context of migraine management in several databases. Results: The findings shed light on the potential of natural supplements as complementary or alternative approaches to traditional migraine therapies, offering insights into a holistic and personalized treatment paradigm for migraine sufferers. Conclusions: Natural supplements have gained attention as potential treatments for migraine relief, often perceived as safer alternatives to conventional medications.